Downsizing human, bacterial, and viral proteins to short water-stable alpha helices that maintain biological potency - Harrison, Rosemary S. (National Academy of Sciences, 2010)
Recombinant proteins are important therapeutics due to potent, highly specific, and nontoxic actions in vivo. However, they are expensive medicines to manufacture, chemically unstable, and difficult to administer with low patient uptake and compliance. Small molecule drugs are cheaper and more bioavailable, but less target-specific in vivo and often have associated side effects. Here we combine some advantages of proteins and small molecules by taking short amino acid sequences that confer potency and selectivity to proteins, and fixing them as small constrained molecules that are chemically and structurally stable and easy to make. Proteins often use short α-helices of just 1–4 helical turns (4–15 amino acids) to interact with biological targets, but peptides this short usually have negligible α-helicity in water. Here we show that short peptides, corresponding to helical epitopes from viral, bacterial, or human proteins, can be strategically fixed in highly α-helical structures in water. These helix-constrained compounds have similar biological potencies as proteins that bear the same helical sequences. Examples are (i) a picomolar inhibitor of Respiratory Syncytial Virus F protein mediated fusion with host cells, (ii) a nanomolar inhibitor of RNA binding to the transporter protein HIV-Rev, (iii) a submicromolar inhibitor of Streptococcus pneumoniae growth induced by quorum sensing pheromone Competence Stimulating Peptide, and (iv) a picomolar agonist of the GPCR pain receptor opioid receptor like receptor ORL-1. This approach can be generally applicable to downsizing helical regions of proteins with broad applications to biology and medicine.